2017
DOI: 10.3892/etm.2017.4758
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of changes of autophagy in rat models of CLP versus LPS induced sepsis

Abstract: In the present study, two different rat models of sepsis, cecal ligation and puncture (CLP), and lipopolysaccharide (LPS), were established. Changes in autophagy in both models were compared using transmission electron microscopy (TEM), immunohistochemistry, western blotting, and quantitative polymerase chain reaction techniques. Consequently, TEM analysis revealed autophagic bodies in the CLP and LPS sepsis models. In addition, autophagy-related protein LC3 A-specific staining was detected in the cytoplasm. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…24 A previous study revealed significant increases in autophagic activity at 12 and 24 h following CLP. 25 Although transient autophagy may have a protective effect, continuous activation of autophagy causes apoptosis in an inflammatory microenvironment. 26 The current study also found that inhibition of Hsp70 promoted autophagy, consistent with previous results.…”
Section: Discussionmentioning
confidence: 99%
“…24 A previous study revealed significant increases in autophagic activity at 12 and 24 h following CLP. 25 Although transient autophagy may have a protective effect, continuous activation of autophagy causes apoptosis in an inflammatory microenvironment. 26 The current study also found that inhibition of Hsp70 promoted autophagy, consistent with previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin may also maintain the integrity of the intestinal epithelial TJ barrier by promoting the expression of TJ proteins, including claudin-3, ZO-1 and occludin. CLP-induced sepsis is the most commonly used animal modelling method for sepsis (28). This model accurately represents the progression and properties of human sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of LPS, though, is a simpler and easier approach. This makes the LPS model better than the CLP model concerning the perturbation of the underlying molecular biological mechanisms in the brain of the model animals [27]. Therefore, we have used exactly the LPS intraperitoneal injection to establish a sepsis model in mice in our research.…”
Section: Discussionmentioning
confidence: 99%